Sifat-Sifat Pendidik - Iskandar Jayadi (LPPM IAIN Sorong, 2018)
This paper discusses the educational qualities of the Quranic perspective of Q.S. Fushshilat ([41]: 34-35). This article is motivated by the number of educators who only rely on intellectual ability in educating, without balancing with other aspects that support the process of education, teaching and learning, such as the nature and a good personality that must be owned by every educator. All the behavior of educators is very influential on learners, because learners tend to imitate educators. Educators are expected by the Islamic education of educators who are able to optimize all the ability in him in order to get the output in accordance with the goals of Islamic education. This study aims to determine the nature of educators contained in the Fushshilat (41: 34-35) which can be applied by every educator in the educational process. This paper shows that in the content of Fushshilat ([41]: 34-35) there are several traits as an educator exemplified by the Prophet Muhammad. (2) Always do good, (3) gentle, (4) affection towards learners, (5) able to hold anger, and (6) have a good attitude the nature of forgiveness, and its implications in the Islamic education system.